IOT-Based Automated Aquarium Care System - Paaventhan, (Progress in Engineering Application and Technology, 2023)
Fishkeeping is a fun and well-established hobby with a vast variety of marine lives to be kept and enjoyed. Fishkeeping can also be psychologically and emotionally comforting as watching aquarium can help people to relax and make beautiful decoration. However, maintaining an aquarium requires consistent effort and knowledge, which can be challenging for aquarists who are not always able to monitor their fish tanks. To address this problem, an IoT-based Automated Aquarium Care System was developed with the objective of developing a system that is reliable and maintains the aquarium's health even in the owner's absence. The system incorporates an auto-feeder, battery-powered aerator, and water change mechanism, all controlled and monitored through the Blynk app. The project successfully achieved its objectives, enabling precise feeding, vital oxygen exchange, and water quality maintenance through rigorous testing and implementation. Moreover, the system operates efficiently during power outages, ensuring continuous functionality. With remote monitoring and control capabilities, users can easily access the system through the Blynk app. The IoT-based Automated Aquarium Care System provides a reliable and efficient solution, alleviating the burden of aquarium maintenance while promoting the health and safety of marine life. This project highlights the significance of automation in aquarium care and contributes to a sustainable and thriving aquatic environment.